ANALISIS BIAYA PERAWATAN DAN PERBAIKAN JEMBATAN SEI. JANGKANG KEC. BANTAN - Wanda, Ardhi Pratama; Gunawan, Gunawan (Politeknik Negeri Bengkalis, 2023)
This research is to analyze the damage that has occurred to the structural components of the bridge and estimate the costs of maintaining and repairing the bridge, so that what handler should be done based on the view of the damage to the bridge elements and costs economical for the bridge under study. Much research is guided by using numbers, starting from data collection, as well as the appearance of the results of the analysis of bridge maintenance and repair costs. Bridges that are handled can be more relieved in terms of costs and the service life of the bridge can be fulfilled. From the results of the study, it was obtained an estimate of the cost of maintaining/repairing the Sei bridge. The anchors amount to Rp.194,000,000.00 and for bridge maintenance costs which are carried out every 5 years amount to Rp.280,399,790.72 for the next 20 years.